Does labral treatment technique influence the outcome of FAI surgery? A matched-pair study of labral reconstruction versus repair and debridement with a follow-up of 10 years. Issue 2 (29th March 2022) - Laboudie, Pierre; Gauthier, Paul; Kreviazuk, Cheryl; Beaulé, Paul E
ABSTRACT: The aim of this study was to analyze the long-term clinical outcomes of labral reconstruction in patients undergoing femoro-acetabular impingement (FAI) surgery and compare them with labral repair and debridement. This is a single-center, single-surgeon, retrospective match-paired study from a prospectively collected hip preservation database. All patients underwent a hip surgical dislocation for FAI surgery. Eight patients underwent labral reconstruction with the ligamentum teres and were matched on sex, age and body mass index with 24 labral repair and 24 labral debridement (1:3). Failure was defined as conversion to total hip replacement (THR) and patient-reported outcome measures (PROMs) were collected. Mean follow-up was 9.8 years ±2.6 (5.2–13.9). There was a significant improvement in postoperative PROMs in the three groups regarding the WOMAC total, WOMAC function, HOOS-QoL, HOOS-ADL and HOOS-SRA ( P < 0.05). There was no statistical difference between the three groups regarding postoperative PROMs and change in PROMs ( P > 0.05). A total of 10 hips underwent joint replacement surgery at a mean time of 7.9 ± 3.5 years (2.4–12). There was no statistically significant difference between the three groups regarding the conversion rate to THR ( P = 0.64) or time between surgery and conversion to THR ( P = 0.15). Compared to a match-pair group of labral repair and debridement, labral reconstruction with ligamentum teres provides similar survival with conversion to a THR as an endpoint, as well as similar improvement in PROMs. Labral treatment can be safely adapted at the nature of the labral lesion with a treatment 'à la carte'.